Listening Backward: Sonic Intimacies and Cross-Racial, Queer Resonance - Hale Wood, Katelyn (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2020)
Documenting my encounters as a white queer scholar with the sonic archive of the late black American lesbian comic Jackie “Moms” Mabley, this paper explores the cross-racial/sexual politics of sonic historiography. Through what I term listening backward, I examine how sound procures queer sonic intimacies between critic and subject: the repetitive listening, soundwaves directly travelling from one voice to one person, and most pertinently, the historical and sociocultural contexts that make consumption of such exchange possible and/or fraught. This listening practice centres on relational and resonant modes of archiving through sound and asks: (1) How can exploring methods of sonic documentation align performance studies’ commitment to archiving the affective? (2) What might attention to not only the product of such documentation but also its performative processes offer about how the sonic can deepen modes of performance historiography and the racial/sexual politics of listening? (3) What practices of listening can centre queer intimacies and temporalities in the archive?